Adaptive action learning in an online community: facilitating a large cohort to deliver results. (2nd January 2021) - Callaghan, David; Collins, Helen
ABSTRACT: This paper explores the literature around online and blended learning. The impetus came from a cohort of 60 students being led through their dissertation by an e-learning evangelist. Initially the pedagogy closely followed Salmon's Five Stage Model, Wenger's Community of Practice, and traditional Social Constructivism pedagogies. In hindsight, it has been realised that, in practice, these pedagogies have been eclipsed by Action Learning – a far better fit to the emergent tutor and student experiences. It is suggested that where 'expert' students are working at the top of Bloom's taxonomy (criticality, creativity, evaluation, innovation), such as during the creation of a dissertation, action learning is a highly effective overarching pedagogy. Moreover, we propose a model of action learning that may work with massive participant numbers; like the MOOC, adding Massive to the existing acronym of action learning Sets: Massive Action Learning Set: MALS.